Work ability and psychosocial work stress – predictors of retirement intention among older teachers - Steffi Kreuzfeld; Reingard Seibt (International Journal of Occupational Medicine and Environmental Health)
Objectives Many teachers worldwide retire early for health or personal reasons. Predictors could help to identify teachers at risk in order to counteract this development. The study therefore investigates whether the intention to retire can be predicted by work ability, psychosocial work stress and work behaviour.